IMPLIKASI PERUBAHAN UNDANG-UNDANG PERPAJAKAN TERHADAP KEPUTUSAN STRATEGI STRUKTUR MODAL PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Fitri Oktariani; Sutrisno .; Aulia Fuad Rahman (Akademi Akuntansi YKPN Yogyakarta, 2015)
This study aims to test and prove leverage ratio empirically in the capital structure of each company at 2009 and 2011 period of tax reform act. The study population was all the companies listed on the Indonesia Stock Exchange in 2008 to 2011 with a sample of 53 manufacturing companies. Sampling using judgment sampling method and data analysis method used is the independent sample t test and paired sample t test.The results of this study indicate that leverage ratio of large companies is higher than small companies in the period of tax reform act in 2011. Accordingly, regulation of tax reform act that lowering tax rates lead to large companies who have the most dominant role increasing the leverage ratio in Indonesia. Keywords: tax reform act, capital structure, leverage.